IMPLEMENTASI PENDIDIKAN AGAMA ISLAM TERHADAP KARAKTER ISLAMI SISWA DI SEKOLAH DASAR - Zalfa Zahirah; Gabriella Aisyah Matos; Nadya Aulia Sari; Jihan Alya (STKIP Subang, 2025)
This study aims to analyze the implementation of Islamic Religious Education(PAI) in shaping the character of students at the elementary school level.Character education is a fundamental aspect in the formation of a child'spersonality that needs to be instilled early on, and PAI has a strategic role in thisprocess. This study uses a qualitative descriptive method with a previous journalanalysis approach (literature review). Data collection was carried out through aliterature study of scientific journals, research articles, and academic publicationsthat are relevant to the implementation of Islamic Religious Education in shapingthe character of elementary school students. The results of the study indicate thatthe implementation of PAI in shaping the character of students is carried outthrough several main strategies, namely the integration of Islamic values ​​inlearning, teacher role models, the habit of worship and noble morals, and religiousextracurricular activities. This study shows that PAI has a significant contributionto the formation of the character of elementary school students when implementedcomprehensively and sustainably.